2021
DOI: 10.2298/sos2103355p
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adsorption performance and quantum chemical modeling of pesticides removal using Cell-MG hybrid adsorbent

Abstract: Magnetite (MG) modified cellulose membrane (Cell-MG), obtained by reaction of 3-aminosilane and subsequently with diethylenetriaminepentaacetic acid dianhydride functionalized waste Cell fibers (Cell-NH2 and Cell-DTPA, respectively), and amino-modified diatomite was used for Azoxystrobin and Iprodione removal from water. Cell-MG membrane was structurally and morphologically characterized using FT-IR and FE-SEM techniques. The influences of operational parameters, i.e. pH, contact time, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, it was recently shown that Fe 3 O 4 modified cross-linked COO-functionalized cellulose membrane manifested moderate removal efficiency for the Azoxystrobin and Iprodione pesticides [38]. In an analogous manner, 38.6 mg g − 1 adsorption capacity of Azoxystrobin uptake using A-LMS_Fe 3 O 4 in batch experiments is an additional proof of material versatility.…”
Section: The Adsorption Performances Of A-lms_fe 3 O 4 and A-lms_mno ...mentioning
confidence: 84%
“…In addition, it was recently shown that Fe 3 O 4 modified cross-linked COO-functionalized cellulose membrane manifested moderate removal efficiency for the Azoxystrobin and Iprodione pesticides [38]. In an analogous manner, 38.6 mg g − 1 adsorption capacity of Azoxystrobin uptake using A-LMS_Fe 3 O 4 in batch experiments is an additional proof of material versatility.…”
Section: The Adsorption Performances Of A-lms_fe 3 O 4 and A-lms_mno ...mentioning
confidence: 84%
“…There are many different methods for the removal of heavy metal ions from water, such as coagulation, flocculation, ion exchange, membrane filtration, and separation. Modification of the surface of the inorganic materials can be physical or chemical, that enables to be adjusted for the various specific use of adsorbent for heavy metals [9]. Consequently, adsorption is the most efficient and economical method of wastewater purification [10].…”
Section: Introductionmentioning
confidence: 99%